A Woman in the Man's Culture of Engineering Education - L. N. Bannikova; E. V. Kemmet (Moscow Polytechnic University, 2019)
The study is aimed at identifying barriers to the research career of women in the academic environment of a technical university. The authors present the results of their study of the women's status in the academic community. The study is based on a quantitative (questionnaire survey) and qualitative (biographical interviews) analysis of the opinions of students and teachers of STEM disciplines of a technical university about the features and problems of women's professional careers. It is established that women of the same university evaluate the presence and degree of influence of barriers to the research careers differently. In some cases, women assessing their professional status note that they do not feel professional discrimination on the basis of gender. In general, the analysis revealed that women who received a STEM education use a strategy of avoiding a research career and choosing alternative career options: either outside the academic environment, or by transitioning to teaching as a way to circumvent gender barriers in grant and publication activities.